2017
DOI: 10.18632/oncotarget.21012
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic nomogram for acute-on-chronic hepatitis B liver failure

Abstract: Background & AimsTo establish an effective prognostic nomogram for acute-on-chronic hepatitis B liver failure (ACHBLF).Materials and MethodsThe nomogram was based on clinical data of 203 ACHBLF patients who admitted to the First Affiliated Hospital of Fujian Medical University from 2009 to 2014. The area under the receiver-operating characteristic curve (AUC) and calibration curve were carried out to verify the predictive accuracy ability of the nomogram. The result was validated in internal and external valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…There are studies estimating the severity and outcomes of HBACLF by establishing prognostic scoring models. Previous studies illustrated that the liver volume [ 19 ], lymphocyte-monocyte ratio [ 20 ], albumin-bilirubin score [ 21 ], logistic regression model [ 22 ], macrophage inflammatory protein 3 α [ 23 ], and other methods [ 24 26 ] could be simple and sensitive models to evaluate the severity and prognosis of ACLF, which would be practically useful in clinic. Those methods mainly concentrated on the severity of liver injury, and the parameters in those models were generally to reflect the condition of liver function.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies estimating the severity and outcomes of HBACLF by establishing prognostic scoring models. Previous studies illustrated that the liver volume [ 19 ], lymphocyte-monocyte ratio [ 20 ], albumin-bilirubin score [ 21 ], logistic regression model [ 22 ], macrophage inflammatory protein 3 α [ 23 ], and other methods [ 24 26 ] could be simple and sensitive models to evaluate the severity and prognosis of ACLF, which would be practically useful in clinic. Those methods mainly concentrated on the severity of liver injury, and the parameters in those models were generally to reflect the condition of liver function.…”
Section: Discussionmentioning
confidence: 99%
“…Five related studies had been carried out to evaluate the prognosis of ACLF patients with nomogram (13,(25)(26)(27)(28). The relatively small number of cases in these studies led to some important risk factors not being included in the models (such as liver cirrhosis, HBV DNA load, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had shown that nomogram enabled more-accurate individualized prediction of survival than MELD, MELD-Na, CTP, sequential organ failure assessment, or CLIF-C scores for HBV patients and demonstrated superior net benefits over other score models[ 25 , 26 ]. Therefore, an effective prognostic nomogram for ACLF patients was established, as shown in Figure 1 ; the nomogram of our study could accurately predict 1- and 2-mo survival in patients with ACLF.…”
Section: Discussionmentioning
confidence: 99%